UKRAINE – REPUBLIC OF POLAND: THE IDEA OF STRATEGIC PARTNERSHIP IN POLITICS OF MEMORY - Федорищак, Х. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the character, features, problems of the modern stage of Ukraine and the Republic of Poland relations, analysed basic directions of strategic partnership in area of politics of memory The relations of Ukraine and the Republic of Poland are based on millennial history that overcame all spheres of life. Ukrainians and Poles – two big European nations, that is bound by centuries-old tradition and that by the close cultural ties and common future in a united Europe. Community of strategic interests, mental closeness objectively mark Republic Poland the main foreign partner of Ukraine in Central and Eastern Europe. Ukrainian- Polish relations traditionally feel on itself the load of difficult pages of general history. For guidance of both the states it follows to take into account as positive so negative experience of the past for creation of new relations that would be built on strategic partnership. Therefore, one of the main objectives is to solve complex Ukrainian-Polish past. From the beginning of overthrow of the communist mode Poland in every way supported the idea of Ukraine on independence. The first step to reconciliation was done, when parliament of Poland condemned an operation "Vistula", what Ukrainian guidance answered on, that by joint efforts Ukraine and Poland will overcome the consequences of tragic the pas and will put beginning the new stage of relations between both people and states. Polish-Ukraine strategic partnership in area of politics of memory develops within the framework of bilateral mutual relations. Modern development of cooperation between Ukraine and the Republic of Poland is in the understanding of gain experience and a new paradigm of relations. About it testifies the wide field of legislative acts in area of politics of memory that are based on a collaboration between public organs, institutes of memory, public organizations.History of the Ukrainian-Polish relations of the last two decades proves that we succeeded to leaf over the not simple pages of the pas, and in basis of modern collaboration to put traditions of mutual cooperation and support.